Conserved and differing functions of the endocrine system across different social systems – oxytocin as a case study - Sosnowski, Meghan J.; Brosnan, Sarah F. (Frontiers in Endocrinology, 2024)
A key goal of the field of endocrinology has been to understand the hormonal mechanisms that drive social behavior and influence reactions to others, such as oxytocin. However, it has sometimes been challenging to understand which aspects and influences of hormonal action are conserved and common among mammalian species, and which effects differ based on features of these species, such as social system. This challenge has been exacerbated by a focus on a relatively small number of traditional model species. In this review, we first demonstrate the benefits of using non-traditional models for the study of hormones, with a focus on oxytocin as a case study in adding species with diverse social systems. We then expand our discussion to explore differing effects of oxytocin (and its response to behavior) within a species, with a particular focus on relationship context and social environment among primate species. Finally, we suggest key areas for future exploration of oxytocin’s action centrally and peripherally, and how non-traditional models can be an important resource for understanding the breadth of oxytocin’s potential effects.